ANALISIS RESPONS KEGIATAN TERHADAP PEMBELAJARAN JARAK JAUH MATA PELAJARAN IPA MELALUI RADIO MALOWOPATI FM BOJONEGORO - Prastiwi Nur Fajar Aulia; Dyah Astriani (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aimed to analyze the student responses in one of the public Junior High Schools in Bojonegoro to distance learning activities for science subjects through Radio Malowopati FM Bojonegoro. This research design used a one-shot case study. The data analysis method used is a triangulation approach with data collection techniques in the form of observation, interviews, and distributing questionnaires to students. This research involved a questionnaire respondent of 110 students and interview respondents were 1 science teacher and 3 students. The resulting response is in the form of a positive response, neutral, or negative response. The results showed that respondents gave a positive response to the aspects of interest, novelty, and usefulness of the existence of distance learning activities for science subjects through Radio Malowopati FM Bojonegoro.